PENERAPAN MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN KOGNITIF SISWA KELAS V MIN 18 PIDIE - Syarifah Rahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
This study aims to determine the aplication of the Group Investigation learning model to improve the cognitive of 5th grade students of MIN 18 Pidie. This type of research is Classroom Action Research (CAR). With data collection techniques in the form of tests, observations and field notes. The subjects of the study were 20 class V students consisting of 7 male students and 13 female students. The results of the study from the average value of students in cycle I were 61.5 with a percentage of 40%. In cycle II the average value obtained by students was 71.1 with a percentage of 72.8%. And in cycle III the average value obtained by students was 80 with a percentage of 100%.